THE REASONING OF THE USAGE OF MEDIAPSYCHOLOGICAL TECHNOLOGIES IN THE PROCESS OF TRAINING OF STUDENTS TO THEIR PROFESSIONAL ACTIVITY - Subashkevych, Iryna (Educological discourse, 2018)
The article deals with the importance of mediaeducation in the educational environment. The theoretical bases are grounded and some practical tips are provided concerning the problem of the formation of the value-content sphere of the students of the pedagogical field by means of mediapsychological technologies. The role of mediapsychological technologies as the factors of the formation of the value-content sphere of our young generation is outlined. The main functions of mediaeducation and mediapsychological technologies are described ( information, activation, the increase of motivation, interactive monitoring, effectiveness, impulse). The most important factors of the influence of media on the formation of values of youth are outlined. The main approaches of implementing of curricula in Ukrainian higher educational establishments are analyzed.